Methods of hysterectomy: systematic review and meta-analysis of randomised controlled trials - Johnson, Neil (BMJ Publishing Group Ltd., 2005)
Objective To evaluate the most appropriate surgical method of hysterectomy (abdominal, vaginal, or laparoscopic) for women with benign disease. Design Systematic review and meta-analysis. Data sources Cochrane Menstrual Disorders and Subfertility Group Trials Register, Cochrane Central Register of Controlled Trials, Medline, Embase, and Biological Abstracts. Selection of studies Only randomised controlled trials were selected; participants had to have benign gynaecological disease; interventions had to comprise at least one hysterectomy method compared with another; and trials had to report primary outcomes (time taken to return to normal activities, intraoperative visceral injury, and major long term complications) or secondary outcomes (operating time, other immediate complications of surgery, short term complications, and duration of hospital stay). Results 27 trials (total of 3643 participants) were included. Return to normal activities was quicker after vaginal than after abdominal hysterectomy (weighted mean difference 9.5 (95% confidence interval 6.4 to 12.6) days) and after laparoscopic than after abdominal hysterectomy (difference 13.6 (11.8 to 15.4) days), but was not significantly different for laparoscopic versus vaginal hysterectomy (difference -1.1 (-4.2 to 2.1) days). There were more urinary tract injuries with laparoscopic than with abdominal hysterectomy (odds ratio 2.61 (95% confidence interval 1.22 to 5.60)), but no other intraoperative visceral injuries showed a significant difference between surgical approaches. Data were notably absent for many important long term patient outcome measures, where the analyses were underpowered to detect important differences, or they were simply not reported in trials. Conclusions Significantly speedier return to normal activities and other improved secondary outcomes (shorter duration of hospital stay and fewer unspecified infections or febrile episodes) suggest that vaginal hysterectomy is preferable to abdominal hysterectomy where possible. Where vaginal hysterectomy is not possible, laparoscopic hysterectomy is preferable to abdominal hysterectomy, although it brings a higher chance of bladder or ureter injury.